2009
DOI: 10.1097/smj.0b013e318197fae4
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Mothersʼ Comfort Discussing Contraception with Infant Providers at Well-Child Visits

Abstract: Many mothers miss or delay their postpartum visits but see their infants' doctor multiple times within the first year. Mothers are comfortable talking with infant providers about contraception. By discussing contraception with mothers at well-child visits, physicians may encourage mothers to use contraception and prevent unintended pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Similar results are found in the present research that the advice on FP during ANC/PNC sessions has improved both contraceptive behavior outcomes. Advice during PNC is found to be more effective followed by, advice received during ANC to improve contraceptive behavior as found in previous studies [ 65 68 ]. This has a programmatic implications that advice on FP during PNC and ANC visits should be promoted with more efforts to increase contraceptive use and to reduce unmet need for FP.…”
Section: Discussionsupporting
confidence: 74%
“…Similar results are found in the present research that the advice on FP during ANC/PNC sessions has improved both contraceptive behavior outcomes. Advice during PNC is found to be more effective followed by, advice received during ANC to improve contraceptive behavior as found in previous studies [ 65 68 ]. This has a programmatic implications that advice on FP during PNC and ANC visits should be promoted with more efforts to increase contraceptive use and to reduce unmet need for FP.…”
Section: Discussionsupporting
confidence: 74%
“…One such approach is the co-location (broadly defined) of postpartum contraceptive services with the Well-Baby-Visit. A study by Fagan et al [ 9 ] found that 75 % of women reported they would be very/somewhat likely to use a contraceptive prescription provided by their infants’ physician. Additionally, a study conducted at UIC Hospital [ 22 ] found that 83 % of postpartum women surveyed at the WBV reported they were comfortable discussing contraception at the WBV, and 84 % stated they would accept contraceptive advice at the WBV.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the timing of the recommended four to six-week postpartum visit in the U.S. is not based on current evidence about women’s sexual activity after pregnancy or the need for timely postpartum contraception; thus, over half of women are at risk for a rapid repeat pregnancy [ 11 ]. Few studies examine women’s preferences for postpartum care [ 9 , 21 , 22 , 31 , 43 ]; however, there is ample evidence that the postpartum visit is underutilized [ 4 , 5 , 7 , 17 , 27 , 30 , 41 , 42 , 44 ]. For example, among women in Illinois who are Medicaid recipients, fewer than 60 % receive a postpartum visit according to the Healthcare Effectiveness Data and Information Set [HEDIS] measure for postpartum care [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in pediatric practices also found high maternal receptivity to health advice at well-child visits. 20,[28][29][30][31][32][33][34][35] This association suggests that well-child visits are an underused opportunity to address maternal risks for poor subsequent birth outcomes. The ICC approach we explored is consistent with recommendations by the American Academy of Pediatrics, which strongly advocates screening for maternal conditions such as smoking and depression at well-child visits.…”
mentioning
confidence: 99%